1993
DOI: 10.1161/01.hyp.22.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Renal nitric oxide and angiotensin II interaction in renovascular hypertension.

Abstract: In two-kidney, one clip (2K1C) renovascular hypertension, blood flow is reduced to the clipped but not to the nonclipped kidney, despite elevated angiotensin II. To determine possible interactions between endothelium-derived nitric oxide and angiotensin, we studied bilateral renal blood flow using radioactive microspheres in anesthetized 2K1C hypertensive rats 4 weeks after clipping. We studied the response to nitric oxide synthesis inhibition with 10 mg/kg body wt JV G -nitro-L-arginine-methyl ester (L-NAME) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
48
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 18 publications
8
48
0
Order By: Relevance
“…18,19 Administration of Ang II receptor antagonists has been shown to restore normal blood pressure and normal renal hemodynamics in humans with essential hypertension, as well as in experimental rats with spontaneous hypertension, 20 with hypertension induced by chronic NOS inhibition, 16 and with renovascular hypertensive disease. 21 Our results suggests that, as in conventional vascular tissue, a relative increase in Ang II in the modi®ed vascular tissue of the corpus cavernosum may contribute to erectile dysfunction. Furthermore, such impaired relaxation and/or augmented contractility of the cavernosal smooth muscle may be amenable to treatment with agents that block the effect of Ang II (Ang II receptor antagonists) or impede the production of Ang II (ACE inhibitors).…”
Section: Discussionmentioning
confidence: 56%
“…18,19 Administration of Ang II receptor antagonists has been shown to restore normal blood pressure and normal renal hemodynamics in humans with essential hypertension, as well as in experimental rats with spontaneous hypertension, 20 with hypertension induced by chronic NOS inhibition, 16 and with renovascular hypertensive disease. 21 Our results suggests that, as in conventional vascular tissue, a relative increase in Ang II in the modi®ed vascular tissue of the corpus cavernosum may contribute to erectile dysfunction. Furthermore, such impaired relaxation and/or augmented contractility of the cavernosal smooth muscle may be amenable to treatment with agents that block the effect of Ang II (Ang II receptor antagonists) or impede the production of Ang II (ACE inhibitors).…”
Section: Discussionmentioning
confidence: 56%
“…This differs from our previous observations in 2K1C rats with severe renal artery stenosis. 22 In those studies, we found normalized blood flow in the nonclipped (but not the clipped) kidney that was largely maintained by EDNO.…”
Section: Discussionmentioning
confidence: 65%
“…This is contrary to what we have previously observed in 2K1C rats with a more severe stenosis in which basal renal blood flow to the nonclipped kidney is similar to controls, with an exaggerated response to L-NAME. 22 In these studies the response to L-NAME was used as an index of the participation of endogenous EDNO in regulating regional hemodynamics. Contrary to our results, it has been reported that agonist-induced, endothelium-dependent vasodilation is impaired in various forms of hypertension.…”
mentioning
confidence: 99%
“…[21][22][23] In extracavernosal segments of the vascular bed, the tone and contractility of VSM and, then, the modulation of regional blood Candesartan and cavernous tissue in SHR JE Toblli et al flow depend on a balance between angiotensin II and NO. [24][25][26] There is compelling evidence supporting that corpus cavernous produces and secretes physiologically relevant amounts of angiotensin II and that the local renin-angiotensin system is involved in the regulation of CSM tone through angiotensin II receptor subtype 1. 27,28 Intracavernosal injection of angiotensin II causes contraction of CSM and terminates spontaneous erection in anesthetized dogs, while administration of an angiotensin II receptor antagonist results in smooth muscle relaxation and, therefore, erection.…”
Section: Discussionmentioning
confidence: 99%